2020
DOI: 10.1089/wound.2019.1021
|View full text |Cite
|
Sign up to set email alerts
|

Skin Structure–Function Relationships and the Wound Healing Response to Intrinsic Aging

Abstract: Significance: Chronic wounds, such as diabetic foot ulcers, venous stasis ulcers, and pressure ulcers affect millions of Americans each year, and disproportionately afflict our increasingly older population. Older individuals are predisposed to wound infection, repeated trauma, and the development of chronic wounds. However, a complete understanding of how the attributes of aging skin affect the wound healing process has remained elusive. Recent Advances: A variety of studies have demonstrated that the dermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 133 publications
0
71
0
4
Order By: Relevance
“…21,23 As aging progresses, intrinsic changes in cell function and metabolism result in dysfunction during the different stages of the healing process. 24 During the inflammatory stage of wound healing, aged macrophages have a decreased phagocytic ability and lower growth factor production compared to young macrophages. 25 Reepithelialization is also delayed as the capacity of keratinocytes and dermal fibroblasts to proliferate and migrate is significantly attenuated with advanced age.…”
Section: Clinical Problem Addressedmentioning
confidence: 99%
“…21,23 As aging progresses, intrinsic changes in cell function and metabolism result in dysfunction during the different stages of the healing process. 24 During the inflammatory stage of wound healing, aged macrophages have a decreased phagocytic ability and lower growth factor production compared to young macrophages. 25 Reepithelialization is also delayed as the capacity of keratinocytes and dermal fibroblasts to proliferate and migrate is significantly attenuated with advanced age.…”
Section: Clinical Problem Addressedmentioning
confidence: 99%
“…These changes may be induced by the passage of time (chronological aging) and/or chronic exposure to solar UV irradiation (photo-aging) [17,18], and they result in functional deficits that make the skin more susceptible to injury and can delay or impair the healing process [19]. As a result, older individuals are predisposed to wound infection, trauma and the development of chronic wounds [6]. Thus, efforts to improve wound healing among older individuals can support the structure and function of aged skin and yield anti-aging effects.…”
Section: Discussionmentioning
confidence: 99%
“…This quantitative tissue monitoring method may be used to evaluate tissue regeneration after skin injury [26,27] and is considered to be a powerful modality for imaging the function and structure of skin tissues during wound healing. We also estimated the effect of seletinoid G on collagen density in UVB-irradiated human skin equivalents by applying second harmonic generation (SHG) imaging, which can be used to provide high-resolution three-dimensional maps of collagen cross-link autofluorescence [6,28]. A previous report showed that seletinoid G increased type I procollagen and reduced matrix metalloproteinase (MMP)-1 expression in skin in vivo [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated skin regeneration efficacy of CS using the epidermal skin models. Because of the progressive decrease in the proliferation capacity of keratinocytes during the skin ageing process, the epidermis becomes thinner [23]. Based on this knowledge, we constructed the aged epidermis model to observe the changes in epidermis by CS treatment.…”
Section: Cs Promotes Epidermal Regeneration In the Aged Skin Modelmentioning
confidence: 99%